Age at Onset of Declarative Gestures and 24-Month Expressive Vocabulary Predict Later Language and Intellectual Abilities in Young Children With Williams Syndrome - Becerra, Angela M.; Mervis, Carolyn B. (Frontiers in Psychology, 2019)
Background: One of the most consistent findings in the early language acquisition literature is that the onset of declarative pointing gestures precedes the onset of expressive referential language. Furthermore, frequency of early use of declarative gestures is a stronger predictor of later lexical development than is early vocabulary size. These findings suggest early declarative gestures may play a critical facilitative role in later language development. To evaluate the universality of these findings, we tested children with Williams syndrome (WS), a genetic disorder associated with both language and communicative gesture delay. Method: Participants were 47 children with classic-length WS deletions. Age of onset of declarative show and point were determined by parental report on the MacArthur-Bates Communicative Development Inventory (CDI): Words and Gestures. Expressive vocabulary size at onset of these gestures, first referential expressive word, 24 months, and 48 months and grammatical complexity at 48 months was determined by parental report on the CDI: Words and Sentences. Receptive and expressive vocabulary and overall intellectual ability at 48 months were measured using standardized assessments. Results: In contrast to previous findings, most children with WS began to produce referential language several months before they produced declarative point. A series of multiple regressions indicated that both age at onset of declarative point and expressive vocabulary size at 24 months made significant independent contributions to individual differences in lexical, grammatical, and overall intellectual ability at 48 months. Similarly to findings for typically developing children and children with other developmental disabilities, individual differences in the declarative gesture measure accounted for considerably more variance in 48-month lexical ability than did early expressive vocabulary size. Discussion: The transition from prelinguistic communication to initial referential language does not depend on the onset of the ability to use declarative point. Nevertheless, the length of time that a child has been producing declarative point was a better predictor than early expressive vocabulary of later lexical abilities. Thus, despite their earlier divergence in their path to language development from the typical one, the path for children with WS re-converges with that for typically developing children and children with other developmental disabilities.